Comparison of Unit Link Product in Indonesia: Study of Insurance and Unit Link products Performance - Sricista, Madiasta; Soekarno, Subiakto (Journal of Business and Management, 2013)
Risks can come at any time, living in Indonesia have a greater risk than living in many developed countries because the government has reduced the lives risks. All of the risks are a blessing for some companies that offer insurance. Development of insurance in Indonesia cannot be separated from the rising level of economic performance, so that the insurance industry continued to a significant increase over the last 5 years. Growth of the insurance industry, making more types of insurance offered. Unit Link products is one of the booster of production premium in the life insurance industry. Unit Link products are modern insurance that combine with insurance and investment inside. Through investment product combined with insurance, raises many pros and cons regarding the products performance optimization. To determine the performance of the Unit Link products, it will be carried out performance analysis of each product in term of insurance and investment. There are four bancassurance companies were selected as research sample; Axa Mandiri, BNI Life, CIMB Sun Life, and Commonwealth Life. Also Prudential become the benchmark to determine the performance of bancassurance. From each company will take one Unit Link product as samples to be compared. In terms of the performance of the insurance will be based on the performance optimization of the product indicated by the allocation dues cost of insurance and amount of insurance money that can be generated. The performance of the investment will be based on returns generated in accordance with the investment allocation of each company. The data is used as the basis of net asset value (NAV) based on historical data. Returns generated will be used as a variable comparison with each product and also be analyzed by the method of risk adjusted performance, namely Sharpe Index. The results of the calculation will be used as a comparison of each Unit Link products and will be compared to the market index (IHSG) as a benchmark.Â Keywords: Unit Link, insurance, Sharpe Index, performance, bancassurance--------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.